Knoevenagel‐Michael‐cyclocondensation Tandem Reaction of Malononitrile, Various Aldehydes and Dimedone Catalyzed by Sulfonic Acid Functionalized Pyridinium Chloride as a New Ionic Liquid and Catalyst. Issue 5 (17th April 2015) - Zolfigol, Mohammad Ali; Khazaei, Ardeshir; Moosavi‐Zare, Ahmad Reza; Afsar, Javad; Khakyzadeh, Vahid; Khaledian, Omid
Abstract New ionic liquid sulfonic acid functionalized pyridinium chloride [Pyridine–SO3H]Cl was used for the synthesis of tetrahydrobenzo[b]pyran derivatives by the one‐pot three component condensation reaction of various aldehydes, dimedone and malononitrile at 95 ºC under solvent‐free conditions.